The tillering phenotype of the rice plastid terminal oxidase (PTOX) loss‐of‐function mutant is associated with strigolactone deficiency. Issue 1 (18th December 2013) - Tamiru, Muluneh; Abe, Akira; Utsushi, Hiroe; Yoshida, Kakoto; Takagi, Hiroki; Fujisaki, Koki; Undan, Jerwin R.; Rakshit, Sujay; Takaichi, Shinichi; Jikumaru, Yusuke; Yokota, Takao; Terry, Matthew J.; et al.
Summary: The significance of plastid terminal oxidase (PTOX) in phytoene desaturation and chloroplast function has been demonstrated using PTOX‐deficient mutants, particularly in Arabidopsis. However, studies on its role in monocots are lacking. Here, we report cloning and characterization of the rice ( Oryza sativa ) PTOX1 gene. Using Ecotype Targeting Induced Local Lesions IN Genomes (EcoTILLING) and TILLING as forward genetic tools, we identified the causative mutation of an EMS mutant characterized by excessive tillering, semi‐dwarfism and leaf variegation that corresponded to the PTOX1 gene. The tillering and semi‐dwarf phenotypes of the ptox1 mutant are similar to phenotypes of known strigolactone (SL)‐related rice mutants, and both phenotypic traits could be rescued by application of the synthetic SL GR24. The ptox1 mutant accumulated phytoene in white leaf sectors with a corresponding deficiency in β‐carotene, consistent with the expected function of PTOX1 in promoting phytoene desaturase activity. There was also no accumulation of the carotenoid‐derived SL ent ‐2′‐ epi ‐5‐deoxystrigol in root exudates. Elevated concentrations of auxin were detected in the mutant, supporting previous observations that SL interaction with auxin is important in shoot branching control. Our results demonstrate that PTOX1 is required for both carotenoid and SL synthesis resulting in SL‐deficient phenotypes in rice.